2018
DOI: 10.1038/s41396-018-0317-4
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of root-colonizing Pseudomonas protegens in herbivorous insects throughout different developmental stages and dispersal to new host plants

Abstract: The discovery of insecticidal activity in root-colonizing pseudomonads, best-known for their plant-beneficial effects, raised fundamental questions about the ecological relevance of insects as alternative hosts for these bacteria. Since soil bacteria are limited in their inherent abilities of dispersal, insects as vectors might be welcome vehicles to overcome large distances. Here, we report on the transmission of the root-colonizing, plant-beneficial and insecticidal bacterium Pseudomonas protegens CHA0 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 49 publications
(86 reference statements)
1
63
0
Order By: Relevance
“…P. protegens and P. chlororaphis colonize the insect gut after oral intake and transmigrate into the hemolymph, causing systemic infections and the eventual death of several Lepidoptera, Diptera, Coleoptera, and Hemiptera insect species [15][16][17][18][19][20][21][22][23]. The P. fluorescens subgroup [2] harbors insecticidal strains with lower pathogenicity than the P. protegens/P.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…P. protegens and P. chlororaphis colonize the insect gut after oral intake and transmigrate into the hemolymph, causing systemic infections and the eventual death of several Lepidoptera, Diptera, Coleoptera, and Hemiptera insect species [15][16][17][18][19][20][21][22][23]. The P. fluorescens subgroup [2] harbors insecticidal strains with lower pathogenicity than the P. protegens/P.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on P. protegens CHA0 and other P. protegens / P. chlororaphis strains related insecticidal activity and host persistence to additional factors, including type VI secretion components [ 28 ], chitinase and phospholipase C [ 16 ], hydrogen cyanide [ 29 ], the cyclic lipopeptide orfamide [ 29 , 30 ], the toxins rhizoxin [ 31 ] and IPD072Aa [ 32 ], and specific lipopolysaccharide O-antigens [ 33 ]. P. protegens / P. chlororaphis strains can also cause nonlethal infections [ 18 , 22 , 23 , 31 ]. Even if the infection does not kill the insect after oral uptake, strains such as CHA0 can persist until pupal and imago stages, thus affecting the insect development as shown for Delia radicum , Plutella xylostella and Pieris brassicae , and be transmitted to new host plants by D. radicum [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. fluorescens SF4c produces more than one functional bacteriocin (such as S-type bacteriocin and phage-tail-like bacteriocin-Tailocins) by their regulator PrtR gene [75]. Flury et al (2019) showed the role of insects such as cabbage root fly, Delia radicum in different developmental stages by harboring persistant root-colonizing P. protegens CHA0 as dispersal agents to new host plants [76].…”
Section: Antibiosismentioning
confidence: 99%
“…Pseudomonas is a bacterial specie which can compete for limited carbon source and is capable of catabolizing a wide range of plant root exudates. This ability has made pseudomonas one of the most successful root colonizers [24,25].…”
Section: Chemical Communication Between Plants and Microbesmentioning
confidence: 99%